Clinical outcomes and cost-effectiveness analysis for the treatment of basilar tip aneurysms. (25th June 2019) - Abecassis, Isaac Josh; Sen, Rajeev; Kelly, Cory Michael; Levy, Samuel; Barber, Jason; Ghodke, Basavaraj; Levitt, Michael; Kim, Louis J; Sekhar, Laligam N
Abstract : Background: Endovascular treatment of basilar tip aneurysms is less invasive than microsurgical clipping, but requires closer follow-up. Objective: To characterize the additional costs associated with endovascular treatment of basilar tip aneurysms rather than microsurgical clipping. Materials and methods: We obtained clinical records and billing information for 141 basilar tip aneurysms treated with clip ligation (n=48) or endovascular embolization (n=93). Costs included direct and indirect costs associated with index hospitalization, as well as re-treatments, follow-up visits, imaging studies, rehabilitation, and disability. Effectiveness of treatment was quantified by converting functional outcomes (modified Rankin Scale (mRS) score) into quality-adjusted life-years (QALYs). Cost-effectiveness was performed using cost/QALY ratios. Results: Average index hospitalization costs were significantly higher for patients with unruptured aneurysms treated with clip ligation ($71 400 ± $47 100) compared with coil embolization ($33 500 ± $22 600), balloon-assisted coiling ($26 200 ± $11 600), and stent-assisted coiling ($38 500 ± $20 900). Multivariate predictors for higher index hospitalization cost included vasospasm requiring endovascular intervention, placement of a ventriculoperitoneal shunt, longer length of stay, larger aneurysm neck and width, higher Hunt-Hess grade, and treatment-associated complications. At 1 year, endovascular treatment was associated with lower cost/QALY than clip ligation in unruptured aneurysms ($52 000/QALY vs $137 000/QALY, respectively, p=0.006), but comparable rates in ruptured aneurysms ($193 000/QALY vs $233 000/QALY, p=0.277). Multivariate predictors for higher cost/QALY included worse mRS score at discharge, procedural complications, and larger aneurysm width. Conclusions: Coil embolization of basilar tip aneurysms is associated with a lower cost/QALY. This effect is sustained during follow-up. Clinical condition at discharge is the most significant predictor of overall cost/QALY at 1 year.